If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying c + -139 = 9 + -3 Reorder the terms: -139 + c = 9 + -3 Combine like terms: 9 + -3 = 6 -139 + c = 6 Solving -139 + c = 6 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '139' to each side of the equation. -139 + 139 + c = 6 + 139 Combine like terms: -139 + 139 = 0 0 + c = 6 + 139 c = 6 + 139 Combine like terms: 6 + 139 = 145 c = 145 Simplifying c = 145
| 8x+12y=2400 | | 2r=3 | | 900b+65=1053 | | 3+6k-6-10k+9+5k= | | 2(x+1.3)=x+3.8 | | 1.5k-2.4=2.1 | | 2x^2+10x-350=0 | | -5x+3=43 | | Y=20(0.85)x | | x-8+(-8x)-15x=-9 | | (5x^2)+11x-36=0 | | (-5x^2y)3= | | 1.4k+-2.4=2.1 | | -2(4-5n)=-88 | | 3d-13=26 | | 4x+64=112 | | ln(3x-2)=1.4 | | n^2+5n+24=0 | | -7b-9=b-113 | | 1/170-1/158= | | o=-7n+4-5n | | -4(x-2)+5x= | | 0.3x+7.8=11.4 | | (4x^2)-7x-36=0 | | 3x+6=x+5+5 | | -4m+5-3m-12= | | 107=6(3x+7)-7 | | 3x^2+5x+13=16 | | -7p-9=b-113 | | 7*20= | | 7-4(7-3)=23 | | -8x-40=2x |